Consumption of vegetables among adolescents in non-coed dormitories at the University of the Philippines Los Banos - Barrion, Aimee Sheree A. (Journal of Human Ecology, 2012)
Looking at the period of adolescence as a window of opportunity to promote good health and reduce the risk of chronic disease, insights into some of the determinants of intake particularly of vegetables of adolescents in non-coed university dormitories. The study was carried out among 128 adolescents using an interview schedule. Self-reported frequency and determinants of vegetable consumption among adolescents residing in non-coed university dormitories was low to cover daily recommendations. Three percent of the male respondents reported that they consume vegetables twice a day. Twenty-eight percent of female respondents reported that they consume vegetables once or twice a week and those who consume vegetables once a day consisted 17%. Bittergourd and squash were the primary contributors to total vegetable intake. The vegetable dishes usually purchased by the adolescents were pinakbet, chopsuey, and ginataang gulay. The usual serving portion of vegetable was 1/2 cup cooked. Health followed by cost were the major reasons given by female respondents for choosing vegetable dishes. Male adolescents, on the other hand, considered price and availability as major reasons given by female respondents for choosing vegetable dishes. Male adolescents, on the other hand, considered price and availability as major considerations in selecting vegetable dishes. Since majority of adolescents spend their time in school, access to and availability of a variety of vegetable dishes in the school cafeterias or canteens should be promoted.